Cleavages developed in mudstone during diagenesis and deformation:: an example from the Carboniferous (Tournaisian), southeastern New Brunswick, Canada - Park, Adrian (Atlantic Geology, 2009)
ABSTRACT The Weldon Formation of the Lower Carboniferous (Tournaisian) Sussex Group of southeastern New Brunswick consists of red mudstone intervals interbedded with red siltstone and fine-grained sandstone. Some of the mudstone intervals exceed 50 m in thickness and are deformed in such a way as to render bedding ambiguous. At two localities south of Moncton, these thick mudstone intervals carry two fracture cleavages that are almost perpendicular to each other, and perpendicular to bedding. In the Weldon Creek section these cleavages are particularly well preserved, and a clear timing relationship can be established. The second cleavage crenulates and transposes the first, which typically carries a slicken lineation where lithons are deformed by crenulation. Thin section and scanning electron microscope images reveal that these cleavages are defined by microveins of calcite, gypsum, and montmorillonitic clays with hematite and vivianite, and that there is some evidence for silica dissolution. At Belliveau Village, these two cleavages are largely disrupted by layer-parallel shear planes in the limb of the Belliveau syncline, indicating that they predated folding. The presence of primary diagenetic gypsum, primary carbonate cement in interbedded sandstone, and low equivalent vitrinite reflectance (%R) values in underlying oil shale (0.65–0.77) indicate that these cleavages formed below 100 °C during diagenesis rather than under anchizone conditions. Their presence reflects a bulk shortening parallel to bedding prior to fold development, and layer-parallel deformation during folding progressively destroyed them. These early cleavages are not precursors to slaty cleavage, and are essentially ephemeral features, though they could provide another anisotropy on which later cleavages might nucleate.